La responsabilité des intermédiaires en droit d'auteur : étude de droit comparé - Jones, Laura Isabelle (Université Paris 1 ; Ludwig-Maximilian-Universität München, 2019)
Les titulaires de droits se tournent de plus en plus vers les intermédiaires techniques pour obtenir la suppression d'un contenu illicite en ligne. voire des dommages et intérêts. La question qui se pose est donc de savoir sur quel fondement juridique les intermédiaires peuvent voir leur responsabilité engagée. Celle-ci se compose de trois piliers majeurs : la responsabilité directe pour communication au public. article 3 de la directive « Infosoc », la responsabilité indirecte pour violation d'une obligation de vigilance (régimes nationaux) et le régime des ordonnances (de blocage), article 8 § 3 de la directive « lnfosoc ». Le présent travail illumine tout d'abord les différentes bases légales au niveau international, européen et national, leur interprétation par la CJUE et leur transposition en France, en Allemagne et au Royaume-Uni. Il se tourne ensuite vers la nécessité d'adaptation des différentes notions telles que la communication au public et l'obligation de vigilance afin d'obtenir un régime cohérent et équilibré. La proposition faite est de suivre une approche économique qui prend en compte la proximité de l'intermédiaire de l'atteinte primaire. Les services qui visent la commission de contrefaçons de la part de leurs utilisateurs et qui en tirent un profit commettent une communication au public. Les plateformes restant en dessous de ce seuil ont à leur charge des obligations de vigilance qui se traduisent notamment en une participation à un régime de notification et de retrait, voire de notification et d'action. En dernier lieu, les intermédiaires qui fournissent seulement l'infrastructure de l'Internet ne sont tangibles que par les biais des injonctions. Primary infringers of copyright often remain anonymous on the Internet. Hence, copyright holders have turned their focus towards intermediaries in order to obtain the blockage of infringing content or damages. There is, however, not one single legal basis for their claims. "Intermediaries' liability" rather consists of different provisions, some at international or European, some at national level. This thesis shows that the legal regime of intermediaries' liability consists of three main pillars: primary liability for communicating a work to the public (art. 3 of the lnfosoc-Directive), secondary liability for violating a duty of care (national law) and (blocking) injunctions (art. 8 § 3 of the Infosoc-Directive). Their interpretation by the CJEU and their national implementations are, however, not adapted to one another. After examining the legal regimes in the European Union, France, Germany and the United Kingdom, the present thesis thus suggests a restructured system following an economic approach. It focusses on the intermediary's proximity to the primary infringement. Platforms that build their operating principles upon illegal actions of their users and exploit these infringements are close enough to the illegal contents. Their actions are hence considered a communication to the public. Intermediaries that operate desirable business models can, on the other hand, only violate copyright on a secondary level by infringing duties of care. These duties typically arise within a "notice and take down" or "notice and action" procedure. Thirdly, intermediaries that merely provide the Internet infrastructure can only be held accountable by the means of injunctions.
Keywords: Blocking injunctions; Communication au public; Communication to the public; Contenu généré par l'utilisateur; Copyright Law; Droit d'auteur; Duties of care; Hyperlinks; Intellectual property; Liability; Liens hypertextes; Obligations de vigilance; Ordonnances de blocage; Propriété intellectuelle; Responsabilité Civile; User generated content; YouTube

Direito, arte e indústria: o problema da divisão da propriedade intelectual na economia criativa - Valente, Luiz Guilherme Veiga (Universidade de São Paulo, 2019)
Os regimes da propriedade intelectual enfrentam problemas de adaptação no cenário contemporâneo. O surgimento da Economia Criativa, de um lado, e a evolução do próprio conceito de arte, de outro, provocaram uma aproximação entre artigos industriais e obras artísticas, passando estas a serem produzidas também dentro de uma lógica comercial. Essas mudanças não foram acompanhadas pelo Direito, resultando em institutos jurídicos que hoje não se aplicam apropriadamente, ao tutelarem excessivamente bens considerados como artísticos (tais quais esculturas, desenhos, fotografias e filmes), ao mesmo tempo em que dispensam tratamento menos restritivo para produtos semelhantes, de setores econômicos em ascensão, como artigos de design. Este trabalho confirma a hipótese de que tal descompasso se deve à manutenção da divisão histórica das categorias da propriedade intelectual (a propriedade industrial e os direitos autorais), engessando a visão clássica da separação entre arte e indústria. Como solução, propomos uma série de diretrizes para orientar eventuais reformas legislativas, como também a doutrina e a jurisprudência, visando a reduzir a defasagem tanto entre os dois regimes jurídicos, quanto entre sua fundamentação original e a realidade atual de sua tutela. Intellectual property legal regimes in Brazil struggle to adapt to the current society. The emergence of the Creative Economy as well as the evolution of the concept of art have brought together industrial items to artistic works. Such changes have deep implications that are not reflected in Law. Legal regimes associated with intangible goods do not apply properly nowadays, as they rigorously protect objects considered as artistic (such as sculptures, drawings, photographs and films), but do not provide the same treatment for similar items provided by new economic sectors, like design products. This research argues that such discrepancy is due to the maintenance of the historical division between the categories of intellectual property, particularly, author's rights and industrial property, deepening the classic distinction between industry and art. As a solution, we advance a series of guidelines for reformers, legislators, scholars and judges, in order to reduce the gap between the two legal regimes, and the mismatch between their original rationale and the reality they currently protect.
Keywords: Copyright; Culture economy; Direito autoral; Economia da cultura; Industrial property; Intellectual property; Propriedade industrial; Propriedade intelectual

The copyright protection of musical works : a historical and contextual analysis - Baloyi, Jele Joel (University of South Africa, 2019)
This work is concerned with an analysis of the copyright protection of musical works. Musical works form part of the categories of works protected under copyright law. It would be easy to dismiss musical works as not warranting a serious study, as would for example, be warranted for “industrial property” rights such as patents and geographical indicators, or more “serious” copyrights such as architectural works and computer software. Such a perspective would however, not be cognisant of the significant contribution that the music industry, as part of the broader cultural and creative industries makes to the global economy. It has, for example, been shown that in 2013, the global cultural and creative industries contributed some US$2,250b, employing some 29,5 million people, with the music industry being one of the top three employers and with its revenues exceeding those of radio.1 A single successful musician can earn in excess of US$100m per annum,2 making the industry ripe for litigious claims. For this reason therefore a consideration of the legal rules that apply to the protection of musical works is crucial. There is currently no clear exposition and systematic analysis of the legal principles applicable to the field of music copyright and no work devoted to the in-depth delineation of the rights and sub-rights relating to musical copyright protection. This study seeks to address this research and knowledge gap by providing a historical and contextual analysis of the protection of musical works. The aim is to provide a complete picture of the milieu of music copyright protection to enable the reader to feel empowered in dealing with the subject-matter. This the writer does by mapping the historical development of music copyright protection in particular from eighteenth century England when the first copyright legislation was enacted, until the enactment of the British Copyright Act of 1911, which signalled the emergence of the “common law” copyright system. The writer then shows how this enactment shaped the development of modern music copyright law, and concludes by presenting a contextual consideration of the current South African law of music copyright and highlighting the challenges it is faced with.
Keywords: Copyright; Copyright protection; Dramatico-musical works; Imperial Copyright Act; Intellectual property; Intellectual property rights; Music; Music trade; Musical compositions; Musical works

Les droits de la propriété intellectuelle et l'intérêt général : approche en droit d’auteur et en droit des brevets - Rikabi, Mouaz (Aix-Marseille Université, 2019)
L’évolution d’une économie industrielle vers une économie de la connaissance et du savoir a propulsé la propriété intellectuelle sur le devant de la scène. Désormais les droits intellectuels s’intègrent à tous les domaines de la vie moderne. De ce fait, le besoin de les protéger efficacement par des règles juridiques appropriées et d’inciter en conséquence les créateurs à produire de nouvelles créations est devenu une nécessité de premier ordre. Cependant, la spécificité de la nature de l’œuvre protégée par la propriété intellectuelle exige la prise en considération de multiples intérêts antagonistes. C’est pourquoi le législateur a cherché, au nom de l’intérêt général, à créer un juste équilibre interne entre les principaux intérêts présents au sein du régime de la propriété intellectuelle. Or, l’exercice des prérogatives octroyées par le régime de propriété intellectuelle effectué par le titulaire de droit a généré une importante expansion de ses intérêts au détriment des autres intérêts concurrents – présents dans la matière. Cette situation a provoqué, en conséquence, une rupture de l’équilibre interne de ce système, préétabli en amont par le législateur. Or, l’intérêt général peut jouer un rôle central dans le rétablissement d’un équilibre en la matière. Dans cette perspective, le juge peut, grâce à son pouvoir créateur de règles jurisprudentielles, se servir de l’intérêt général comme d’une ligne directrice servant à rétablir ce juste équilibre dans le système de la propriété intellectuelle. L’intérêt général justifie donc, tout autant que les limites intrinsèques aux droits de la propriété intellectuelle, les limites extrinsèques à ces droits
Keywords: Abus de droit; Abuse of rights; Biotechnologie; Biotechnology; Brevets d'invention; Competencia; Competition law; Computer programs; Concurrence (droit); Conditions de protection; Conditions of protection; Copyright; Droit; Droit de l’Homme; Droit des brevets; Droit d’auteur; Droits d'auteur; Exceptions; Freedom of expression; Human rights; Intellectual property; Intérêt général; Liberté d’expression; Patent law; Programmes d’ordinateur; Propriedade intelectual; Propriété intellectuelle; Public health; Santé publique

Third Party’s Intellectual Property Rights And The Seller’s Liability Under The United Nations Convention On International Sale Of Goods (CISG) And The Sale Of Goods Act (SGA) - Kiraz, Serife E. (University of Leicester, 2019)
This thesis is a comparative analysis of the provisions on the seller’s duty to deliver the goods free from any third-party intellectual property rights (IPRs) under the United Nations Conventions on the International Sale of Goods (CISG) and the UK Sale of Goods Act 1979 (SGA). As a consequence of technological advancement, there has been an increased observance of the interaction between intellectual property rights (IPRs), which are intangible property rights, and tangible goods. As a result of this interaction, growing numbers of goods, which are either subject to IPRs as a whole or that possess an IP-protected component, have become subject to sales agreements. The circulation of the goods around the world increases the likelihood that third-party IPRs over the goods will be infringed. This risk of infringement also raises the possibility that the application of IP law remedies will prevent the buyer from reselling or using the goods in question. This study is concerned with the question of how the sale of goods is affected by third-party IPRs, and it proposes to undertake a comparative analysis of the provisions that determine the seller’s liability when third-party IPRs arise in relation to goods that are sold under the CISG and the SGA. It seeks to determine which instrument offers sufficient protection that will benefit the buyer. In attempting to reveal the sufficient protection, it also undertakes a comparative analysis of the remedies that are available to the buyer under the CISG and the SGA when third-party IPRs over the goods are raised. With regard to the widely acceptance of the CISG by 89 states, and the dominant role of English law in commercial law and its preference as a governing law to most contracts, it is aimed to determine the differences and similarities between the CISG and the SGA, and the practical consequences of their application to the contracts when third-party IPRs over the goods arise. The thesis will seek to determine if the text of the relevant CISG articles can be improved and will accordingly formulate proposals that work towards this outcome.

Copyright as a constraint on creating technological value - Drążewski, Kasper (European University Institute, 2019)
How do we legislate for the unknown? This work tackles the question from the perspective of copyright, analysing the judicial practice emerging from case law on new uses of intellectual property resulting from technological change. Starting off by comparing results of actual innovation-related cases decided in jurisdictions with and without the fair use defence available, it delves deeper into the pathways of judicial reasoning and doctrinal debate arising in the two copyright realities, describing the dark sides of legal flexibility, the attempts to ‘bring order into chaos’ on one side and, on the other, the effort of judges actively looking for ways not to close the door on valuable innovation where inflexible legislation was about to become an impassable choke point. The analysis then moves away from the high-budget, large-scale innovation projects financed by the giants of the Internet era. Instead, building upon the findings of Yochai Benkler on the subject of networked creativity, it brings forth a type of innovation that brings together networked individuals, sharing and building upon each other’s results instead of competing, while often working for non-economic motivations. It is seemingly the same type of innovation, deeply rooted in the so-called ‘nerd culture’, that powered the early years of the 20th century digital revolution. As this culture was put on trial when Oracle famously sued Google for reuse of Java in the Android mobile operating system, the commentary emerging from the surrounding debate allowed to draw more general conclusions about what powers the digital evolution in a networked environment. Lastly, analysing the current trends in European cases, the analysis concludes by offering a rationale as to why a transformative use exception would allow courts to openly engage in the types of reasoning that seem to have become a necessity in cases on the fringes of copyright.
Keywords: Copyright; Fair use (Copyright); Intellectual property

The challenge of three-dimensional printing : questioning established concepts in intellectual property law - Elam, Viola (European University Institute, 2019)
Over the last years, academics, practitioners and policy makers have focused their attention on an emerging technology: three-dimensional printing (“3DP”). 3DP is often portrayed as a game changer, showing the potential to disrupt established socioeconomic paradigms and exert profound implications in disparate areas of law. 3DP not only is well integrated in the manufacturing industry, but also increasingly adopted at consumer level. Recent developments have made it possible for ordinary people to take an active role in the production, customization and distribution of goods, and likewise paved the way for the proliferation of new market entrants, such as 3DP online platforms. Against this background, this thesis aims to shed some light on the implications that 3DP may have for Intellectual Property Law. In particular, this work attempts to predict and grasp the consequences that the digitization of real world things may carry in the area of IP law, both from the side of protection and infringement. This contribution is intended to create general awareness about the current state of the art and likewise delineate possible future scenarios in the 3DP ecosystem. The research question at the core of the analysis is whether the current legal framework of different IPRs already offers suitable means for regulating the thin dividing line between the digital and the analogue world, or rather needs to be amended, in order to cope with such a fascinating reality. To this end, the analysis contributes insights to the best legal treatment that CAD files shall receive, in case such files embed products protected by copyright, designs, patents and trademarks. Hence, it addresses right owners’ concern that the online transmission of CAD files, combined with the ease of converting such files into the final printout, will facilitate mass-scale and worldwide infringement of all IPRs.
Keywords: 3D; Copyright; Intellectual property; Three-dimensional printing